Distribution and Alteration of Lymphatic Vessels in Knee Joints of Normal and Osteoarthritic Mice1. Issue 3 (March 2014) - Shi, Jixiang; Liang, Qianqian; Zuscik, Michael; Shen, Jie; Chen, Di; Xu, Hao; Wang, Yong‐Jun; Chen, Yan; Wood, Ronald W.; Li, Jia; Boyce, Brendan F.; Xing, Lianping
<x xml:space="preserve">Abstract</x> Objective To investigate the distribution and alteration of lymphatic vessels and draining function in knee joints of normal and osteoarthritic mice. Methods For the mouse models of osteoarthritis (OA), we used mice with meniscal‐ligamentous injury or mice with conditional knockout of the gene for cartilage transforming growth factor β (TGFβ) type II receptor. The severity of cartilage loss and joint destruction was assessed histologically. Capillary and mature lymphatic vessels were identified and analyzed using double immunofluorescence staining and a whole‐slide digital imaging system. Lymphatic drainage of knee joints was examined using near‐infrared lymphatic imaging. Patient joint specimens obtained during total knee or hip arthroplasty were evaluated to verify the content validity of the mouse findings. Results Lymphatic vessels were distributed in soft tissues (mainly around the joint capsule, ligaments, fat pads, and muscles of normal knees). The number of lymphatic vessels, particularly the number of capillaries, was significantly increased in joints of mice with mild OA, while the number of mature lymphatic vessels was markedly decreased in joints of mice with severe OA. OA knees exhibited significantly decreased lymph clearance. The number of both capillary and mature lymphatic vessels was significantly decreased in the joints of patients with OA. Conclusion The whole‐slide digital imaging system is a powerful tool, enabling the identification and assessment of lymphatic microvasculature in the entire mouse knee. Lymphatic capillaries and mature vessels are present in various soft tissues around articular spaces. Abnormalities of lymphatic vessels and draining function, including significantly reduced numbers of mature vessels and impaired clearance, are present in OA joints.